Bill O'Reilly's Legends and lies [compact disc, unabridged] : the real West - Fisher, David, 1946- (Macmillan Audio, 2015)
A fascinating, eye-opening look at the truth behind the western legends everyone thought they knew. Included are the ten legends featured in Bill O'Reilly's 'Legends and Lies' docuseries; from Kit Carson to Jesse James, Wild Bill Hickok to Doc Holliday, accompanied by two bonus chapters on Daniel Boone and Buffalo Bill and Annie Oakley.